Female Language Features in Women’s Twitch App Livestreaming - Jenifer Chandra; Linuwih, Endar Rachmawaty (Institut Agama Islam Negeri Palopo, 2024)
Language and gender are related to one another and impacted each other constantly. Society expects women to speak formally and politely including female streamers on Twitch App. There has been many research regarding women linguistic features in movies, blogs, as well as YouTube videos, but there is still no research regarding women linguistic features in Twitch App. This study aims to find out which women’s linguistic features are used by two female streamers on Twitch app and the function. Moreover, the writer applied Descriptive qualitative method and with two female streamers’ streaming videos on Twitch app as objects. The data were collected using observation as well as documentation and the utterances used by the streamers were analyzed using Lakoff’s theory of female language feature and Holmes and Wilson theory regarding function of the use of language. The results were, the two female streamers were found to use female linguistics’ features and the most dominant feature used by both streamers is lexical hedges or fillers. As for the function, the most dominant reason the features used by two streamers was the conversation topic. However, more thorough research should be done especially regarding the background especially the characteristic of each streamer to better understand why they used those utterances.